Improving Economic Resilience of Riyadh Batik MSMEs through Utilization of Digital Technology via Shopee Store Account Creation Workshop - Ferdinand, M. Gadink Nurikhsan; Pranoto, M. Alfaredzi; Lumban Gaol, Melita Br; Fitri, Nur Annisa; Putri, Thea Cresensia; Simanungkalit, Trianovalita; Putri, Rizka; Togatorop, Jesiva Br; Simamora, Rapina; Elisabet, Sopia (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research explores the impact of a Shopee store account creation workshop on the economic resilience of Riyadh Batik MSMEs, addressing challenges and opportunities in digital transformation. Method: Employing a mixed-methods approach, the study combines qualitative observations and interviews with quantitative surveys to assess workshop outcomes and their implications for MSMEs. Practical Applications: Findings inform stakeholders on empowering MSMEs through digital literacy, expanding market reach via online platforms like Shopee, and fostering sustainable growth in local communities. Conclusion: The workshop offers a promising strategy for bolstering MSME resilience, highlighting the significance of digital skills development and infrastructure investment for long-term industry sustainability.